IMPLEMENTASI GAME SIMULASI MATEMATIKA PADA KELAS 5 SEKOLAH DASAR - Vina Sufenti; Tri Yuliati; Tri Handayani; Ari Sellyana (Politeknik Negeri Indramayu, 2024)
Adventure game simulations can have several positive impacts on mathematics learning in schools. They can increase student motivation, develop problem-solving skills, provide hands-on learning experiences, encourage collaboration, and offer immediate feedback. By incorporating adventure game simulations into mathematics education lessons, educators can create engaging and effective learning environments that foster deeper understanding and appreciation of mathematics among students. This research designs an animated simulation game for mathematics subjects in the introduction of fractions, speed and discharge, and scale. This game has an agricultural and livestock theme, where each player will play through 3 stages starting from planting or maintenance animations, cooking, and finally selling. Games built on a desktop basis for use by teachers. This research method uses an educational game design model which focuses on three components, namely game design, pedagogy and learning content. The results of testing the use of mathematics games with students in class received a positive response from the questionnaire data given to 20 grade 5 students with a total of 12 questions. Evaluation of the use of the game uses the heuristic game principle by calculating an average score of 4.2 so it can be concluded that this mathematics simulation game for grade 5 elementary school is suitable for use.